The structure of tuna access agreements in the Western and Central Pacific Ocean: Lessons for Vessel Day Scheme planning - Havice, Elizabeth (Marine policy, 2010)
The tuna industry in the Western and Central Pacific Ocean (WCPO) is one of the largest and most valuable fisheries in the world. Since the 1980s, Pacific island countries have used licensing agreements with foreign fishing interests—known as access agreements—to earn tuna-related revenue and control the environmental impacts of fishing, with only minimal success. To date, there has been little work detailing the structure of access agreements and assessing how this structure relates to economic and environmental outcomes in the sector. This article helps to fill this gap by providing an overview of various access structures and a detailed empirical assessment of how these structures are applied in access agreements between Pacific island countries and the major foreign fishing interests active in the WCPO. This analysis is placed in the context of evolving regional fisheries management structures. The study reveals that while there is no uniform formula for access agreements, each structure is subject to distinct political, economic and environmental considerations that influence outcomes for Pacific island countries. As Pacific island countries develop the mechanism to allocate fishing rights under the new Vessel Day Scheme, drawing on their long history with access agreements will assist efforts to use access to achieve policy objectives. Improved transparency will enable Pacific island countries to identify successes and problems and adapt the Vessel Day Scheme allocation mechanisms accordingly.